A gastronomia como estratégia de promoção da alimentação saudável na moradia universitária - Rita de Cássia Ribeiro (2019)
In this article we intend to describe the methodology and present the results achieved in the extension project, in interface with the research, “Gastronomy in the House”. This action was carried out with the students residing in the university residence of the Federal University of Minas Gerais, in Belo Horizonte, MG, Brazil, with the intention of equipping them to prepare their own meals in this environment. For this, the students were socially and nutritionally characterized, gastronomic workshops were planned and executed, and the effectiveness of these practices as a nutritional intervention strategy was evaluated. The profile of the students who participated in this action revealed an important rate of overweight and obesity grade I and inadequate eating modes related to intake and various habits of consumption. Finally, the gastronomy was presented as an effective mechanism for the learning teaching process about healthy and adequate nutrition in university housing.